Solamargine Alleviated UVB-Induced Inflammation and Melanogenesis in Human Keratinocytes and Melanocytes via the p38 MAPK Signaling Pathway, a Promising Agent for Post-inflammatory Hyperpigmentation - Zhao, Juemin; Dan, Yanjun; Liu, Ziqi; Wang, Qianqian; Jiang, Min; Zhang, Chengfeng; Sheu, Hamm-Ming; Lin, Chrang-Shi; Xiang, Leihong (Frontiers in Medicine, 2022)
Post-inflammatory hyperpigmentation (PIH) is a common acquired pigmentary disorder occurring after skin inflammation or injury. Ultraviolet B irradiation could exaggerate PIH clinically, due to its effect on promoting cutaneous inflammation and melanogenesis in keratinocytes and melanocytes respectively. Solamargine (SM), a steroidal alkaloid glycoside extracted from Solanum undatum, significantly inhibits UVB-induced pro-inflammatory cytokines IL-1α, IL-1β, IL-8, and IFN-γ, as well as paracrine melanogenic factors ET-1, α‑MSH and bFGF in human keratinocytes. Additionally, SM significantly attenuated UVB-induced melanin synthesis in human epidermal melanocytes through down-regulation of tyrosinase activity and expression of MITF, TRP-1, TRP-2 and tyrosinase. The anti-inflammatory effect of SM in UVB-irradiated keratinocytes is exerted through the p38 MAPK-Nrf2-HO-1 signaling pathway. With its anti-inflammatory and whitening effect, SM may improve PIH through both paracrine regulation of keratinocytes and direct action on melanocytes, making it a promising agent for PIH.